ENCOURAGING ANALYTICAL READING SKILLS AMONG STUDENTS - Shomurodova Shahlo Jahonovna; Axmedjanova Farida Djavairovna (Web of Journals Publishing, 2025)
the article discusses the importance of analytical reading skills being developed among students to enhance their understanding, critical thinking, and academic performance in general. As the volume of information has escalated in the era of the digital age, the need for students to be in a position where they can analyze texts instead of possessing surface-level knowledge is key. We present a number of methodologies and methods accessible to teachers by which they can foster analytical reading, including guided discussion, questioning approaches, and cross-disciplinary reading. As teachers maintain the spotlight on analytical reading, they can allow the students to engage maximally with written texts and enhance their analytical capabilities, which could get them ready suitably for sophistications in their academic and working lives.
Keywords: Analytical reading, critical thinking, student engagement, comprehension strategies, educational practices, cross-disciplinary learning.